EXPERIMENTAL STUDY OF EUROPIUM (III) COPRECIPITATION WITH CALCITE - Lakshtanov L.Z.; Stipp S.L.S. (My University, 2004)
Partitioning of Eu(III) in calcite, CaCO3, was evaluated with the aim of collecting data on partition coefficients and to enhance understanding of the incorporation mechanisms. This information will aid in the interpretation of geological processes from rare Earth element (REE) data and in the use of Eu(III) as a chemical analogue for the trivalent actinides, particularly Am(III) and Cm(III). Coprecipitation experiments were carried out by the constant addition method at 25°C and PCO2 = 1 atm. Eu(III) was strongly partitioned from the solution into calcite. For dilute solid solutions (XEu < 0.001), Eu partition coefficients were estimated to be 770 ± 290 and found to be independent of calcite precipitation rate in the range of 0.02 to 2.7 nmol mg−1 min−1. This could be explained by the approximately equal values of the Eu partition and adsorption coefficients. Several solid solution models were tested. A vacancy model for Eu2(CO3)3-CaCO3 is consistent with the experimental results and constraints on geometry for Eu fit in the calcite lattice. For low Eu content, vacancy density is independent of Eu concentration in the solid so logarithm of the ion activity product, log (Eu)2(CO32−)3, depends linearly on log XEu2. The fit of the data to such a model is good evidence that Eu(III) is taken up as a true solid solution, not simply by physical trapping. A model using EuOHCO3-CaCO3 is also consistent with the uptake stoichiometry, but EuOH2+ substitution for Ca2+ would be expected to distort the calcite structure more than is compatible with such a high KD. Several other models, including EuNa(CO3)2-CaCO3, were abandoned because their stoichiometric relationships did not fit the experimental data.